Advantages and disadvantages of use of digital collections in the process of education - Vrana, Radovan (Array, 1999)
In last few years the Internet has become a true component part of the process of education in many countries in Europe. This global computer network has brought us many types of applications of computer technology suitable for learning. However, there are still some methods and procedures which are part of this global network and are still not sufficiently used. As a result of this opinion, a small group of students of the 4th year of library and information sciences at the Faculty of Philosophy in Zagreb, proposed a project which, they think, would solve the problem of inadequate quantity of printed exam materials at the Faculty necessary for the successful completion of exams by use of a digital collection containing equivalent ready-for-use material in electronic form.